Synthetic antibody-derived immunopeptide provides neuroprotection in glaucoma through molecular interaction with retinal protein histone H3.1 - Fomo, Kristian Nzogang; Schmelter, Carsten; Atta, Joshua; Beutgen, Vanessa M.; Schwarz, Rebecca; Perumal, Natarajan; Govind, Gokul; Speck, Thomas; Pfeiffer, Norbert; Grus, Franz H. (Frontiers in Medicine, 2022)
Glaucoma is a group of optic neuropathies characterized by the progressive degeneration of retinal ganglion cells (RGCs) as well as their axons leading to irreversible loss of sight. Medical management of the intraocular pressure (IOP) still represents the gold standard in glaucoma therapy, which only manages a single risk factor and does not directly address the neurodegenerative component of this eye disease. Recently, our group showed that antibody-derived immunopeptides (encoding complementarity-determining regions, CDRs) provide attractive glaucoma medication candidates and directly interfere its pathogenic mechanisms by different modes of action. In accordance with these findings, the present study showed the synthetic complementary-determining region 2 (CDR2) peptide (INSDGSSTSYADSVK) significantly increased RGC viability in vitro in a concentration-dependent manner (p < 0.05 using a CDR2 concentration of 50 μg/mL). Employing state-of the-art immunoprecipitation experiments, we confirmed that synthetic CDR2 exhibited a high affinity toward the retinal target protein histone H3.1 (HIST1H3A) (p < 0.001 and log2-fold change > 3). Furthermore, molecular dynamics (MD) simulations along with virtual docking analyses predicted potential CDR2-specific binding regions of HIST1H3A, which might represent essential post-translational modification (PTM) sites for epigenetic regulations. Quantitative mass spectrometry (MS) analysis of retinas demonstrated 39 proteins significantly affected by CDR2 treatment (p < 0.05). An up-regulation of proteins involved in the energy production (e.g., ATP5F1B and MT-CO2) as well as the regulatory ubiquitin proteasome system (e.g., PSMC5) was induced by the synthetic CDR2 peptide. On the other hand, CDR2 reduced metabolic key enzymes (e.g., DDAH1 and MAOB) as well as ER stress-related proteins (e.g., SEC22B and VCP) and these data were partially confirmed by microarray technology. Our outcome measurements indicate that specific protein-peptide interactions influence the regulatory epigenetic function of HIST1H3A promoting the neuroprotective mechanism on RGCs in vitro. In addition to IOP management, such synthetic peptides as CDR2 might serve as a synergistic immunotherapy for glaucoma in the future.